Kindergarten Teachers’ Competence in Designing Inclusive Lesson Plans through Guided Training: Kompetensi Guru Taman Kanak-Kanak dalam Merancang Rencana Pelajaran Inklusif Melalui Pelatihan Terbimbing - Normayani, Risma; Ishartiwi (Indonesian Journal of Innovation Studies, 2025)
General Background: Inclusive education requires teachers to be equipped with the skills to design lesson plans that accommodate children with special needs (CSN), yet many early childhood educators lack sufficient training. Specific Background: In Indonesia, a significant proportion of kindergarten teachers struggle to create adaptive lesson plans despite policies mandating inclusive practices. Knowledge Gap: Previous studies show the potential of Problem-Based Learning (PBL) to enhance inclusive teaching, but evidence on its effectiveness in structured guided training for kindergarten teachers remains limited. Aims: This study aimed to improve the ability of kindergarten teachers to develop inclusive lesson plans through guided PBL-based training. Results: Using School Action Research with nine teachers at TK Negeri 1 Sangkulirang, findings revealed a substantial increase in competence, with average lesson plan scores rising from 48.09% in cycle I to 75.25% in cycle II. The greatest improvements occurred in defining learning objectives (35.2%), selecting strategies (32.8%), and using adaptive media (40.1%), though responsiveness and personal approaches required further support. Novelty: This study is among the first to systematically apply guided PBL training for early childhood teachers in inclusive classrooms, demonstrating its scalability. Implications: The results highlight guided PBL as a strategic pathway for professional development, aligning with national inclusive education goals and underscoring the need for sustained mentoring, case-based simulations, and collaborative practices to ensure long-term implementation.Highlight : Training improved teachers’ skills in inclusive lesson planning. Major progress in goals, methods, and adaptive media use. Emotional responsiveness still requires more guidance. Keywords : Children with Special Needs, Inclusive Learning, Problem Based Learning, School Action Research, Kindergarten Teachers